Meningkatkan Kemampuan Analisis Kalimat Persuasif dalam Teks Pidato Melalui Model Pembelajaran TGT (Teams Game Tournament) pada Kelas VIII G SMPN 50 Kota Batam - Dinda Nur Dwi; Delia Fitri; Khairun Nisa; Nur Melisa Putri; Tere D’amor Philip; Etik Triwahyuni; Fabio Testy Ariance Loren (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the significant effect of the TGT (Team Game Tournament) learning model on class VIII G at SMP Negeri 50 Batam and the comparison with the lecture method applied in class VIII C on student learning outcomes regarding Persuasive Sentence Analysis in Speech Texts. In this study, the author used a quasi-experimental design approach and applied a pretest and posttest. The research population was taken from 3 classes in class VIII SMP and the class research sample taken was in class VIII G which consisted of 29 students as the experimental class, then class VIII C which consisted of 29 students became the control class. The data analysis technique first carried out a swimmer test which required a normality test and a homogeneity test, then after the normal and homogeneous data were known, it was continued with a hypothesis test (t-test).